Governance configurations and academic outcomes: The example of Ph.D. education - Peter Schneider; Dieter Sadowski (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2010)
In many European countries efforts are undertaken to improve doctoral education. In the context of new public governance in the Higher Education sector, less state, more competition, less academic self-governance, more internal hierarchy and more influence by external stakeholders under the common roof of New Public Management (NPM) are considered most promising for successful PhD education. Therefore according to a steering model of American research universities many initiatives are undertaken to introduce more managerial elements in European university departments. Based on an explorative analysis of qualitative and quantitative data of 26 continental European, English and American economics departments, we investigate the steering effects of the five above mentioned governance dimensions in the years 2001 to 2002 on subsequent placement success of PhD graduates. To control the impact of resources on PhD education, next to governance regimes we added four different resource conditions to the analysis: financial resources, publication record of the department, total number of professors in a department and annual number of PhD graduates in a department, Using fuzzy-set QCA to analyze the data, our results deliver strong support for local best ways of steering configurations and no superiority of one system over the other. Introducing market elements though seems to be important in any governance system but only in combination with different co-conditions. In respect to our control conditions only financial resources contribute considerably to the understanding of steering PhD education. Our results strengthen the strong impact of competition as an effective governance instrument and take into account the relevance of financial resources.
Keywords: 330; New Public Governance; competition; higher education; PhD education; fsQCA